Development of a Speaking Skill Assessment Rubric for Children in English Based on the Universal Design for Learning Approach in Inclusive Schools - Lenny Solo; Ninuk Lustyantie; Fathiaty Murtadho (CV. Rustam, 2025)
This study aims to develop an English-speaking skills assessment rubric for children with autism spectrum disorder (ASD) using the Universal Design for Learning (UDL) approach in an inclusive school setting. The research involved 24 regular students and one student with mild ASD in the 7th grade at Sekolah Alam Bekasi, offering a comparison framework. However, children with ASD have unique cognitive, social, and communication needs that differ from neurotypical students. Comparisons must therefore be approached carefully, considering these differences. The study followed Borg & Gall's Research and Development (R&D) model, starting with a needs analysis, followed by product design, expert validation, product revision, and limited testing. Data was gathered through questionnaires, interviews, and documentation. The needs analysis revealed that both teachers and parents require a flexible, inclusive, and ASD-sensitive assessment tool, especially for evaluating verbal and non-verbal communication skills. The resulting rubric is based on the three UDL principles: Multiple Means of Engagement, Representation, and Action and Expression, with specific, measurable, and context-appropriate indicators. Content validation by three experts in special education, language assessment, and inclusive pedagogy produced Aiken’s V values between 0.85 and 0.95, indicating strong validity. A limited trial with five students with ASD demonstrated the rubric’s effectiveness in assessing individual speaking abilities and guiding teachers in providing adaptive interventions. By incorporating both verbal and non-verbal aspects like gestures and eye contact, the rubric offers a fairer and more holistic assessment for students with ASD.